Increased work of breathing and its relationship to dyspnea in malignant pleural effusion - Gólczewski, Tomasz; Stecka, Anna M.; Grabczak, Elżbieta M.; Zielińska-Krawczyk, Monika; Krenke, Rafał (Frontiers in Physiology, 2025)
ObjectivesAlthough dyspnea is the most common symptom of pleural effusion (PE), its physiological basis has not yet been fully elucidated. The aim of this work is to investigate the cause of dyspnea before therapeutic thoracentesis (TT) by analyzing the lack of dyspnea relief after TT.MethodsWe retrospectively analyzed data gathered during TT. Among others, our database includes measurements of instantaneous pleural pressure (Ppl) in the ipsilateral hemithorax and airflow in the mouth (during TT), as well as arterial gas tensions (AGT) and dyspnea characterized quantitatively via the Modified Borg Scale (before and after TT). As the Borg scale is a subjective measure, the change in dyspnea (dB) was used in reliable quantitative analyses. Differences in various parameters and their changes between patients who reported dyspnea relief and the other patients (the YES and NO groups, respectively) were studied. Additionally, correlations between dB and these parameters (and their changes) were studied.ResultsOnly the amplitude of Ppl changes related to breathing after TT was significantly different (higher) in group NO than in group YES (p < 0.003; the large effect size). dB correlated with this amplitude and the volume of withdrawn fluid (r = −0.51 and 0.51, respectively), but it correlated with neither changes in AGT nor minute ventilation.ConclusionThe results suggest that the key mechanism of dyspnea in patients with malignant PE is related to reduced total lung compliance due to collapse of a lung part, leading to an increase in the work of breathing required to maintain adequate minute ventilation.